PENGARUH PERPUTARAN MODAL KERJA TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Tiana, Alma; Bustang, Bustang; Sabarudin, Sabarudin (Jurnal Akuntansi Kompetif, 2025)
The purpose of this study is to determine the Effect of Working Capital Turnover on the Profitability of Manufacturing Companies Listed on the Indonesia Stock Exchange". This study uses a quantitative research method, the data collected consists of Primary Data and Secondary Data. Primary data comes from observation and documentation. While for secondary data by collecting data through literature studies. The data analysis techniques used are Descriptive statistical analysis and Regression analysis. The results of this study show the effect of working capital turnover and accounts receivable turnover on profitability in manufacturing companies in the consumer goods industry sub-sector listed on the IDX for the period 2017 - 2020 which were studied with the help of SPSS data processing, it can be concluded that Working Capital Turnover partially has a positive and significant effect on profitability for companies listed on the Indonesia Stock Exchange in manufacturing companies in the consumer goods industry sub-sector for the period 2017 to 2020. This shows that when the working capital turnover value is high, the company can get or obtain high profitability too. Based on the results of the study, working capital turnover has an influence on profitability of 73.2%.